Advances in C(sp3)–H Bond Functionalization via Radical Processes - Zhang, Tong; Wu, Yue-Hua; Wang, Nai-Xing; Xing, Yalan (Synthesis, 2019)
C(sp3)–H Bonds are the most common structures in organic molecules. In recent years, the direct functionalization of C(sp3)–H bonds has attracted wide attention and made significant progress. This review mainly focuses on C(sp3)–H bond functionalization of alkanes with or without functional groups via radical processes reported since 2017. In particular, three methods of generating free radicals are discussed: the use of a radical initiator such as TBHP or DTBP; photocatalysis, and via 1,5-hydrogen atom transfer (1,5-HAT).1 Introduction2 C(sp3)–H Bond Functionalization of Alkanes3 C(sp3)–H Bond Functionalization of Alkanes with a Functional Group4 Conclusions
Keywords: C(sp3)–H functionalization; oxidative coupling; transition-metal catalyzed; step economy; green chemistry